Interests, Powers and Mere Equities in Modern Land Law. (10th January 2017) - Cooper, Simon; Lees, Emma
Abstract: English land registration law is a work in progress. There remain important unresolved issues concerning the conceptual building blocks used in the Land Registration Act 2002. This article focuses on rights to correct the land register. It considers the place of such rights in the ordering of estates, interests, rights and equities; and makes proposals about the characteristics of these rights so as to produce an integrated, coherent regime which combines the blunt rule for the passing of property with a sophisticated remedial regime for its recovery. Having analysed the right to rectify, it concludes that the right to rectify shares such similarities with the 'mere equity' that classification as a right to rectify makes sense in explaining the current law. In terms of policy, however, this classification is inappropriate and reform is required. Potential options for such reform are considered.